Implementasi Metode Six Sigma dengan Pendekatan DMAIC untuk Meminimalisasi Kecacatan Produk Pancong Pocong UMKM Ketintang - Ahmad, Imaniar; Muttaqin, Benazir Imam Arif; Chandra, Huki (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
SME’s Pancong Pocong Ketintang, an SME’s in Surabaya, is currently facing problems with its products and packaging. Packaging is often not tight and breaks easily, causing the topping to overflow and the packaging to become dirty. To reduce packaging defects, the Six Sigma method with the DMAIC (Define, Measure, Analyze, Improve, Control) approach is used. This method is effective in reducing defects and improving quality. The result of this research is that the researcher defines the types of defects that exist and determines critical to quality. In the measurement stage, the average DPMO value is 157,088, which means it has a sigma level of 2.51. At the analyze stage, the results obtained from the Pareto diagram showed that the most dominant type of defect was overflowing packaging, amounting to 48%. In the improvement stage, improvements are made using the kaizen five m checklist tool which consists of man, material, method and environment. The final stage, the improvement control provided can be implemented on an ongoing basis by implementing operational standards.